Stray Cat Gastrointestinal Protozoa Prevalence and Infection Degree in Madiun Public Health Center and Traditional Market - Hayuning Nurrodhiya; Legowo, Djoko; Suprihati, Endang; Hastutiek, Poedji; Mufasirin; Rahardjo, Dadik (Universitas Airlangga, 2023)
This study determine the prevalence and protozoa infection degree of gastrointestinal in stray cats at Public Health Center and Traditional Market of Madiun City. 80 fecal sample collected. Fecal samples examined with direct smear, sedimentation, and floatation method. Positive samples calculated using the Lucient-Brumpt method. The result of the examination in Public Health Center showed that 37,5% stray cat infected by Isospora sp., Entamoeba sp., and Cryptosporidium sp., with 1167.33a±168.373 infection degree. The examination result in Traditional Market showed that 62,5% stray cat infected by Isospora sp., Entamoeba sp., and Cryptosporidium sp., with 1186.00a±148.577 infection degree. The result of Chi Square analysis obtained p<0,05 indicated that there were significant differences between stray cat including faecal collection location, age, type of cat and faecal condition. The result of Kruskal Wallis analysis of the degree infection obtained p>0,05 indicated that there were no significant differences.